Strengthening Conflict Resolution in Creating Peace Based on Local Wisdom in Meunasah Mesjid, Aceh Province, Indonesia - Kasim, Fajri M.; Nurdin, Abidin; Rizwan, Muhammad; Abubakar, Muhammad Bin (FISIP Universitas Malikussaleh, 2022)
The local wisdom values of the Acehnese have proven to be used as a mechanism in conflict resolution. The problem of conflict is not only the social reality of the people of Aceh, but it has become a problem for the world community. Many conflicts occur in communities that require deep knowledge and broad insight into adat so that they can be resolved through deliberation and consensus. Knowledge of local wisdom and insight into customary-based conflict resolution is not evenly distributed among gampong apparatus, therefore this community service aims to strengthen the role of local wisdom-based conflict resolution to create peace in Gampong Meunasah Mesjid, Muara Dua sub-district, Lhokseumawe City. The method used is strengthening and capacity building. Stages of implementation, problem identification, program implementation in the form of training. So that it is hoped that capacity and knowledge development will be achieved, improvement of the social and cultural values of the community. The benefits and impacts of this training are that the community will gain a strengthened understanding of customary values and local wisdom that can be used as a means of conflict resolution in the national legal system; strengthening understanding of customary values and local wisdom according to Islamic law; the establishment of partnerships, friendship and cooperation between the campus and the community in maintaining peace in the community; preservation and improvement of values and the role of conflict resolution in sociological and cultural contexts in society.